The alignment of extrinsic motivated behaviour and metacognitive skills among first year undergraduate medical students / Hong Wei-Han - Hong, Wei-Han (2016)
Past literature indicates that there is a probability that medical students who lack alignment between Extrinsic Motivated Behaviour (EMB) and Metacognitive Skills (MS) may underperform which eventually leads to attrition or incompetency. Thus, the purpose of this research was to study the alignment of the EMB and MS of selected first year students enrolled in two undergraduate medical curricula, an existing integrated curriculum (NIC) and a newly introduced competency-based curriculum (UMMP) at a local Malaysian university. The four dimensions of EMB included external, introjected, identified and integrated regulations. The MS consisted of the knowledge and regulation dimensions of metacognition. Specifically, the study sought to (i) profile the student sample for their dimensions of EMB and MS; (ii) to determine the significant differences between the EMB dimensions and year-end achievement for the NIC and UMMP students; (iii) to determine the significant differences between the MS and yearend achievement for the NIC and UMMP students; (iv) to investigate the correlation (if any) between EMB and MS of the students with their year-end examination results; (v) to explore the alignment of EMB and MS for the NIC and the UMMP students, and (vi) to determine the interactions between EMB and MS with the year end result of students in both curricula. A total of 174 students and 159 students following the NIC and UMMP curriculum took part in this study respectively. The mixed model design was used where the Extrinsic Motivated Behaviour Inventory (EMBI) and the Metacognitive Skills Inventory (MSI) were administered to obtain quantitative data, while individual interviews were conducted to obtain qualitative data. The year-end examination results were utilised to represent students’ achievement. The profiling showed that students from both curricula while still showing characteristics of all the EMB dimensions were dominant in one of the dimensions. In the NIC curriculum, the one-way ANOVA analysis showed no significant differences between the four dimensions of EMB and achievement but in the UMMP curriculum, there were significant differences for the same analysis. For both curricula, a t-test revealed significant differences for MS scores with students' achievement. Pearson correlation results revealed that the total score for EMBI and MSI of the NIC curriculum were moderately correlated. In the UMMP curriculum, a small correlation was found between the total score for EMBI with MSI. A higher correlation was found between the total scores of EMBI and MSI with students’ achievement in the UMMP curriculum compared to the NIC curriculum. A MANOVA analysis showed the dimensions of EMB and MS affected students' achievement in both curricula. Overall, the quantitative findings showed students in the UMMP curriculum indicated a better alignment between EMB and MS. Qualitative data revealed that this better alignment of EMB and MS among the students in the UMMP involved greater physical, cognitive and affective interactions. From the findings, implications of the study and suggestions for further research have been put forward.